A Review and Classification of Energy Efficient MAC Protocols for Underwater Wireless Sensor Network - Waheed Hyder; Adnan Nadeem; Abdul Basit; Kashif Rizwan; Kamran Ahsan; Nadeem Mehmood (Journal of Basic & Applied Sciences, 2017)
Underwater wireless sensor network is an emerging wireless networking technology (UWSN). UWSN has various applications for example it can be used for monitoring seismic activities, underwater animal, pipeline etc. UWSN face challenges in their MAC later operations. Different energy efficient MAC protocols have been proposed for underwater wireless sensor networks (UWSN) to overcome the problem of propagation delays which is inherent in underwater acoustic networks. In this paper, we study the energy efficient MAC protocols including EE-MACU, R-MAC and T-Lohi. We classify UWSN MAC protocols into two broad categories contention free and contention based and we further categorize contention based protocol. We analyze and compare key UWSN MAC protocols based on certain parameters and suggest their suitability in various scenarios.